The biotechnology debate democracy in the face of intractable disagreement - Bovenkerk, Bernice (Dordrecht, The Netherlands Springer, 2012)
Annotation This book grounds deliberative democratic theory in a more refined understanding of deliberative practice, in particular when dealing with intractable moral disagreement regarding novel technologies. While there is an ongoing, vibrant debate about the theoretical merits of deliberative democracy on the one hand, and more recently, empirical studies of specific deliberative exercises have been carried out, these two discussions fail to speak to one another. Debates about animal and plant biotechnology are examined as a paradigmatic case for intractable disagreement in todays pluralistic societies. This examination reveals that the disagreements in this debate are multi-faceted and multi-dimensional and can often be traced to fundamental disagreements about values or worldviews. One of the acute insights to emerge from this examination is that deliberation can serve different purposes vis-à-vis different types of problem. In the case of deeply unstructured problems, like the modern biotechnology debate, the aim of inclusion is more appropriate than the aim of consensus. This book highlights the importance of political culture and broader institutional settings in shaping the capacity and propensity of citizens to engage in deliberation and the degree to which governments are prepared to relinquish authority to deliberative mini-publics."Robyn Eckersley, University of Melbourne, Australia.
Keywords: Biotechnology -- Moral and ethical aspects; Philosophy (General); Ethics